The Role of social media A Tool of Cyber Diplomacy for Global Public Opinion Pro Palestine - AL Mughni, Akbar Muhammad Luthfi (Master Program of Sociology, Universitas Malikussaleh,, 2024)
The preference of countries to use cyber diplomacy strategies by utilizing social media, Instagram to support the realization of their national interests has become an international phenomenon today. Cyber diplomacy in the modern era of international relations has turned out to be an instrument for countries to exercise their soft power and convey specific messages aimed at the global public. Thus, cyber diplomacy can be an alternative for countries that have serious challenges conveying formal diplomacy using conventional means. Palestine, as an entity that still has legal status, also utilizes cyber diplomacy as a strategy to gain support and recognition from the international community. This article aims to answer the question of how Palestinian diplomacy can gain support from countries in the world. The results of this research show that Palestinian cyber diplomacy is carried out using the Instagram account @eye.on. Palestine focuses on providing information to the international community regarding the conditions in Palestine. Posts uploaded by the @eye.on.Palestine account can be categorized into four things, namely the suffering of the Palestinian people due to Israeli attacks, damage to infrastructure in Palestine, Israeli attacks on Palestinians and support provided by other countries to Palestine. The cyber diplomacy carried out by Palestine has not been able to stop Israel's attacks on Palestine. Still, through this diplomacy, the Palestinian people have received a lot of support from various countries, which can be seen from the large number of global public opinions that are pro-Palestinian.